Decomposing rice yield gaps into efficiency, resource and technology yield gaps in sub-Saharan Africa - Dossou-Yovo, Elliott Ronald; Vandamme, Elke; Dieng, I.; Johnson, J.M.; Saitoa, K. (Elsevier, 2020)
Meeting current rice demand in sub-Saharan Africa (SSA) requires narrowing yield gaps on currently available agricultural land. The objectives of this study were to decompose rice yield gaps into efficiency, resource and technology yield gaps and to identify priority areas for research and development in the major rice production systems (irrigated lowland, rainfed lowland, and rainfed upland) in SSA. Data were collected during the 2012–2015 wet seasons on soil properties, field operations and yields in 1529 fields at 34 sites in 20 countries using a standardized protocol. Stochastic frontier analysis using data on biophysical environment and fertilizer management practices together with a crop simulation model (ORYZA2000) was used to quantify the yield gap, and efficiency, resource, and technology yield gaps. Cluster analysis was performed to classify the site-production system combinations into yield gap groups. Actual rice yields were on average 3.8, 2.6 and 1.7 t/ha in irrigated lowland, rainfed lowland, and rainfed upland, respectively. The yield yap ranged from 2.0–10.0 t/ha across site-production system combinations while the efficiency, resource, and technology yield gaps varied between 0.9 to 5.7, 0.1 to 2.3 and 0 to 7.5 t/ha, respectively. On average, efficiency, resource, and technology yield gaps accounted for 23, 5 and 37 % of the benchmark yield (potential yield in irrigated lowland or water-limited potential yield in rainfed lowland and upland). Four yield gaps groups were identified and were related to the production systems, soil properties, and fertilizer application. Narrowing yield gaps requires the dissemination of integrated crop management practices in yield gaps groups with a large efficiency yield gap, whereas, in yield gaps groups with a large technology yield gap, the development of technologies to improve soil properties and fertilizer use should be given priority